Voltammetric Determination of Rhodamine B Using a ZIF-67/Reduced Graphene Oxide Modified Electrode - Huynh Truong Ngo; Vo Thang Nguyen; Tran Duc Manh; Tran Thanh Tam Toan; Nguyen Thi Minh Triet; Nguyen Thanh Binh; Nguyen Thi Vuong Hoan (TV); Tran Vinh Thien; Dinh Quang Khieu (My University, 2020)
Voltammetric Determination of Rhodamine B Using a ZIF-67/Reduced Graphene Oxide Modified Electrode
Keywords: Rhodamine B